2017
DOI: 10.1108/apjie-12-2017-040
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of perceived value in the Airbnb context

Abstract: Purpose-This study aims to examine the antecedents of perceived value in the Airbnb context using the variables of perceived benefits (i.e. monetary saving, hedonic benefit, novelty and social interaction) and perceived risks (i.e. performance, physical, psychological and time). Design/methodology/approach-The study population was Airbnb users in South Korea. This study applied a survey research method using a questionnaire. A link to the survey was sent via e-mail to panel members of a multinational research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 45 publications
(81 reference statements)
3
31
1
1
Order By: Relevance
“…This result implies that Airbnb users in Korea are using Airbnb because they have a fun and different experience from it. These results support previous studies showing that the hedonic factor affects cognitive value using Airbnb [9,18,33].…”
Section: Analysis Results Of Consumer Modelsupporting
confidence: 92%
See 2 more Smart Citations
“…This result implies that Airbnb users in Korea are using Airbnb because they have a fun and different experience from it. These results support previous studies showing that the hedonic factor affects cognitive value using Airbnb [9,18,33].…”
Section: Analysis Results Of Consumer Modelsupporting
confidence: 92%
“…Several previous studies have been conducted on the motivation to use Airbnb from the user's perspective. Stollery and Jun found that monetary saving, hedonic benefit and novelty has positive effects on the perceived value of Airbnb for Korean Airbnb guests [18]. However, it has been mentioned as a singular point that social interaction that emphasizes the special advantage of using Airbnb does not affect perceived value for Korean guests.…”
Section: Motivation From Consumer and Provider Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, and according to Guttentag (2019), Airbnb offers an alternative value proposition to guests centered around the potential for a more authentic local experience (hedonism). In this line, in a study with Airbnb users in South Korea, Stollery and Jun (2017) concluded that there is a positive influence of hedonic benefit on perceived value; and it could be translated to the behavioral price. These authors found that South Korean Airbnb guests find value in employing Airbnb because it permits them to have distinct and unique experiences, have fun and excitement and save money (Stollery and Jun 2017).…”
Section: Antededents Of Non-monetary Pricementioning
confidence: 99%
“…Several studies also highlight the missing or negative impact of sharing on social cohesion. Users of Airbnb and Uber often have little to no interest in social interaction [ 105 , 114 , 159 , 165 ]. Accommodation sharing can also reduce the sense of community within cities [ 53 , 56 ].…”
Section: Social Sustainability Frameworkmentioning
confidence: 99%